ANALISIS BAHASA POLITIK PEJABAT PUBLIK INDONESIA BERDASARKAN TINJAUAN FILSAFAT NILAI - Bambang Widiatmoko (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2007)
Political language of Indonesia's public official have a special characteristics so it is need more exploration based on philosophy of value 's perspective. In this paper the writer describe Indonesia ’s public official political language based on philosophy of value. The description is based on two kinds of value ground namely aestethics value and social value.